(3CUhd GdCMcGe aj GdMdGd hGdMQGes - (3CMeO Hf SdjeGf Hf eMeO Hf GdeWgQ Hf jMji Hf GdMSjfs ((3CMeO Hf efUhQ s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdCLd GdaGVd bGd (B: (3G dMeO ddg GdcHjQ GdeJYGd Pi GdYXeI hGdLdGd hGdef hGdEaVGd SQjY GdMSGH TOjO GdeMGd s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef HGH Gdbhd ai GdZfGFe hbSeJgG (B" (3bhdg (B:(3NHQ hCfG GHf CQHY YTQI SfI ade jLRfi s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN YHO GdYRjR GdMHTi GdNGUg HeOjfg BH s
Keywords: (3abg GdePGgH GdCNQis